Numerical Analysis of Subgrade Behavior under a Dynamic Maglev Train Load. (11th May 2022) - Wang, Wubin; Deng, Zhixing; Li, Yandong; Huang, Zhichao; Niu, Yunbin; Xie, Kang
Abstract : Medium-low-speed maglevs are increasingly used in the urban rail transit industry because of their advantages, such as low noise and low energy consumption. In this study, a finite element analysis of the responses of the subgrade that supports a medium-low-speed maglev structure under a dynamic maglev load is presented. First, the finite element analysis considers a low-lying structure with different elastic moduli. Then, the attenuation laws of the dynamic stress and dynamic deformation for different depth ranges of the subgrade under the rail beam are analyzed. In addition, the magnitude of the influence of the dynamic load is clarified. The results lead to a recommendation of a base bed thickness of 1.5 m, graded gravel or group A filler as the surface layer of filler, and gravel soil as the bottom layer. This study provides theoretical support for the construction design of a subgrade structure under the rail beam of a low-lying maglev line.